Butterflies (Lepidoptera: Papilionoidea) of Mount Sago, West Sumatra: Diversity and Flower Preference - Ratih Rusman; Tri Atmowidi; Djunijanti Peggie (Bogor Agricultural University, Indonesia, 2016)
Diversity of butterfly depends on the availability of food plant and habitat quality. The aims of this study were to assess diversity and flower preference of butterflies in Mount Sago, West Sumatra, Indonesia. Observations were performed by scan sampling method in four types of habitats, i.e. secondary forests, pine forests, rubber forests, and agricultural areas. Our results showed that at least 184 species of butterflies and 56 species of nectar plants have been identified in Mount Sago. Nymphalid butterfly, Neptis hylas, was the most dominant species of butterflies. Two species, i.e. Trogonoptera brookiana and Troides amphrysus, were found as the protected butterflies. Diversity of butterfly in secondary forests was highest, whereas the lowest diversity was found in pine forest. Papilionid butterflies were found frequently feeding on tube blossoms, nymphalid butterflies on head blossoms, and lycaenid butterflies on flag blossom. Our results also showed that habitat change impacts composition and diversity of butterfly.